Formal Procedure Versus Victim's Interest: Antinomy of Handling Sexual Violence Cases In East Luwu - Sunardi Purwanda; Handar Subhandi Bakhtiar; Nurul Miqat; Rafika Nur; Manga Patila (Jurnal Hukum Volkgeist, 2022)
Complexity and challenges in uncovering crimes by the police have brought the law enforcement process to purely formal matters. Since the Indonesian police agency separated from the armed forces, their formal and professional attitude has faced many realities on the ground: choosing formal precedence (legal procedures) and ignoring the interests of victims. Legal procedures are more focused on formal justice in accordance with existing, written rules of the game and cannot provide freedom of action. The police are only the spokesperson for written laws and regulations. The idea of ​​being part of people's lives is collided with formal procedures. This condition requires the police to ignore substantial justice, whose importance is more important than mere procedural matters. Law enforcement that is only based on procedures without being balanced with efforts to achieve the goals of law enforcement actually has the potential to damage the order of human rights values. The type of research used is normative legal research using a legal approach, a historical approach, and a philosophical approach. Law enforcement by the police which tends to discriminate against the rights of victims has an impact on the low level of public trust in the police institution which ultimately makes many victims reluctant to report to the police.